PENGEMBANGAN STRATEGI PEMBELAJARAN DALAM PENANAMAN NILAI-NILAI KEAGAMAAN PADA ANAK USIA DINI - Rina Septiana; Neng Awalia Farida (Jurnal El-Audi, 2022)
Upbringing and education fulfill the basic needs and obligations of all Muslims who profess to be the Hanif religion. The purpose of this study was to determine the state of religious values ??in early childhood in Nabila Nagrak Kindergarten, Skabumi Province, to plan the development of learning strategies to teach religious values ??to early childhood, and to teach religious values. hindering the development of learning strategies and internal evaluation, the success rate of developing learning strategies in teaching religious values, and developing learning strategies in teaching religious values. This study uses a qualitative descriptive approach that aims to explain situations and phenomena by adapting the data analysis used to analyze the findings with the existing data is descriptive, but not numbers, but data collected in the form of words and photos. This is due to the use of qualitative methods. In addition, all that is collected can be the key to research. Learning Development at Nabila Nagrak Kindergarten seeks to make students' basic provisions to love the Qur'an and the Sunnah of the Prophet SAW and become readings and life guidelines. Therefore, the syllabus used is a combination of the Kemendikbud syllabus, the TPQ syllabus and a uniquely designed syllabus sourced from the Qur'an and hadith. An example of a self-designed curriculum here is that TK Naviranagrac has developed a special curriculum for preschool children (school age children).